Reducing of Raffinose and Stachyose by Rhizopus oryzae and Lactobacillus plantarum at Soybean Fermentation - Farid Salahudin; Pramono Putro Utomo (Biopropal Industri, 2012)
Soybean (Glycine max) has high levels of protein. Furthermore, it also contains raffinose and stachyose, which in high amounts can lead to flatulence. It is known that Rhizopus oryzae could reduce the levels of stachyose and raffinose in soybean flour processing. Lactobacillus plantarum also could reduce stachyose levels on the processing of yoghurt from soybean.  Therefore the aim of this study was to determine the reduction of raffinose and stachyose on soybean fermentation using R. oryzae and L. plantarum isolates. The study was conducted by using combination of R. oryzae and L. plantarum isolates in soybean fermentation process in different length of time. The levels of raffinose and stachyose on fermented soybean products then tested. The results of this study showed that fermentation using R. oryzae single isolates for 2 days (R2L0) can produce soybean flour with low levels of raffinose and stachyose.  The products also have good color and smell.